2020
DOI: 10.3390/plants9060721
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Anatomical and Physiological Responses Can Predict the Ideal Period for the Transplantation of Hydroponic Seedlings of Hymenaea courbaril, a Neotropical Fruit Tree

Abstract: Hydroponics is an excellent alternative approach for the production of seedlings, given the growing demand for fruiting trees for the reforestation or recuperation of degraded natural landscapes. In most cases, however, little is known about the optimal period for the maintenance of the seedling in the hydroponic system. Given this, we decided to investigate the hypothesis that morpho-anatomical and physiological alterations can be used to predict the optimal timing for the transplantation of the seedlings to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Seedling growth in nurseries is directly influenced by factors such as water, temperature, relative humidity, and luminosity. Knowledge on the behavior of plants in the face of environmental factors is important, as the need to increase and diversify seedling production both for conventional agriculture and for the recovery of areas of natural vegetation degraded by human activity is growing throughout the world ( Sousa et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seedling growth in nurseries is directly influenced by factors such as water, temperature, relative humidity, and luminosity. Knowledge on the behavior of plants in the face of environmental factors is important, as the need to increase and diversify seedling production both for conventional agriculture and for the recovery of areas of natural vegetation degraded by human activity is growing throughout the world ( Sousa et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…H. courbaril is widely exploited due to its commercial and medicinal value and the properties of its wood, sap, bark, fruit, and seeds, which are highly valued. Thus, for its characteristics, this species is a promising candidate for reforestation programs or regeneration of natural habitats (Nascimento et al, 2015;Sousa et al, 2020). Oliveira et al (2011) observed in their review that H. courbaril is included among the 25 priority species for programs to recover areas of degraded forest.…”
Section: Introductionmentioning
confidence: 99%
“…Among native Brazilian species, Jatobá (Hymenaea courbaril L., Fabaceae), is a species with wide distribution throughout the American continent, presenting commercial interest in the timber, medicinal and ecological sectors, with rapid growth, being indicated for the recovery of degraded areas (Sousa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to understand the nutritional requirements of species at different stages of their development, which avoids the unnecessary applications of chemical fertilizers. Hydroponic cultivation is a technique that allows the isolation of external factors such as physics, soil chemistry, control of essential nutrients, and supply of oxygen and water necessary for the full development of the plant (Wootton-Beard, 2019;Sousa et al, 2020). Therefore, this system can be adopted to understand aspects of the absorption, use, and impact of different nutrients throughout the development of plants.…”
Section: Introductionmentioning
confidence: 99%